2018
DOI: 10.1136/bmjebm-2017-110855
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to reporting guidelines and clinical trial registration policies in oncology journals: a cross-sectional review

Abstract: Reporting guidelines (RG) aim to improve research transparency and ensure high-quality study reporting. Similarly, clinical trial registration policies aim to reduce bias in results reporting by ensuring prospective registration of all trial outcomes. Failure to adhere to quality standards documented in RGs may result in low-quality and irreproducible research. Herein, we investigate the adherence to common RGs and trial registration policies in 21 oncology journals. We surveyed the Instructions for Authors pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The EQUATOR Network, the international establishment devoted to the advancement of improving study reporting, is also referenced. Previous studies have confirmed that when journals provide detailed guidance to authors, quality of research reporting is improved 29 30. Second, Addiction encourages authors to use Penelope (www.penelope.ai), a tool created by the EQUATOR Network, to perform an automated inspection of a manuscript on reporting compliance with various reporting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The EQUATOR Network, the international establishment devoted to the advancement of improving study reporting, is also referenced. Previous studies have confirmed that when journals provide detailed guidance to authors, quality of research reporting is improved 29 30. Second, Addiction encourages authors to use Penelope (www.penelope.ai), a tool created by the EQUATOR Network, to perform an automated inspection of a manuscript on reporting compliance with various reporting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the oncology literature adheres to reporting guidelines to improve transparency and ensure accuracy of reporting 26. Ideally, to minimise the effect of publication bias in systematic reviews, reporting guidelines such as PRISMA would make a statement on the issue.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of journal endorsement of reporting guidelines and study registration in the last decade is depicted in figure 2 15–24. Our results showed that the journals we considered were more likely to endorse the CONSORT statement, the most commonly endorsed standard, and other reporting guidelines than journals in prior evaluations and covering other fields.…”
Section: Discussionmentioning
confidence: 79%